Flights of fancy: Corporate jets, CEO perquisites, and inferior shareholder returns - Yermack, David (Journal of Financial Economics, 2006)
This paper studies perquisites of CEOs, focusing on personal use of company planes. For firms that have disclosed this managerial benefit, average shareholder returns underperform market benchmarks by more than 4% annually, a severe gap far exceeding the costs of resources consumed. Around the date of the initial disclosure, firms’ stock prices drop by an average of 1.1%. Regression analysis finds no significant associations between CEOs’ perquisites and their compensation or percentage ownership, but variables related to personal CEO characteristics, especially long-distance golf club memberships, have significant explanatory power for personal aircraft use.